Double Trouble - Okoro, Anezi (African Universities Press, 1990)
Living up to his nickname Willie in Trouble, Wilson Tagbo steals out of school one night to be initiated into a secret cult. But this adventure leads him into far more trouble than he had imagined.
Keywords: Juvenile literature-Fiction-Nigeria (English)